Mathematical Representation Ability in the Implementation of Ethno-Flipped Classroom Model Assisted by Interactive Media Based on Self-Efficacy (Department of Mathematics, Universitas Negeri Semarang, 2023)
This study aims to (1) determine the effectiveness of the Ethno-Flipped Classroom model assisted by interactive media on students' mathematical representation abilities, and (2) describe the mathematical representation abilities of students who have high, medium and low self-efficacy. This study was mixed-methods with sequential explanatory design. Retrieval of quantitative data using a mathematical representation ability test, while collecting qualitative data using self-efficacy questionnaires and interview guidelines. The population in this study were students of class VIII SMP N 2 Susukan, Banjarnegara Regency. The samples of this study were 25 students from the experimental class and 26 students from the control class. The results showed that (1) Ethno-Flipped Classroom assisted by interactive media was effective on mathematical representation abilities, (2) subjects with high self-efficacy were able to fulfill all indicators of mathematical representation abilities, namely verbal, symbolic and visual representations, (3) subjects with medium self-efficacy can fulfill indicators of verbal and symbolic representation, (4) subjects with low self-efficacy only fulfill indicators of verbal representation.